2017
DOI: 10.4103/ijdr.ijdr_34_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of shaping ability of V-Taper 2H, ProTaper Next, and HyFlex CM in curved canals using cone-beam computed tomography: An in vitro Study

Abstract: The canal preparation with V-Taper 2H showed lesser transportation and better centering ability than PN and Hyflex CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…This agrees with another study that reported XP generated less canal transportation than WOG at the 7-mm level using the micro-CT method [32]. And Shenoi et al also demonstrated the superior centering ability of VT compared to ProTaper Next, and HyFlex CM in curved canals [33]. Gundappa et al found that the taper was one of the main factors related to the occurrence of canal transportation in a meta-analysis of the centering ability of NiTi instruments [34].…”
Section: Shaping Abilitysupporting
confidence: 80%
“…This agrees with another study that reported XP generated less canal transportation than WOG at the 7-mm level using the micro-CT method [32]. And Shenoi et al also demonstrated the superior centering ability of VT compared to ProTaper Next, and HyFlex CM in curved canals [33]. Gundappa et al found that the taper was one of the main factors related to the occurrence of canal transportation in a meta-analysis of the centering ability of NiTi instruments [34].…”
Section: Shaping Abilitysupporting
confidence: 80%
“…This may be due to PTN modified tip design and a brushing motion, away from external root concavities, to facilitate flute unloading and apical file progression[ 24 ] which leads to more centered preparation and its M-wire alloy property which increases flexibility[ 16 ] and a reducing taper of PTN file in coronal portion leads to more flexibility in the apical region[ 25 ] which causes less apical transportation. Even the apical 3 mm of the PTN instrument has square cross-section which gives more core strength in narrow apical part.…”
Section: Discussionmentioning
confidence: 99%
“…Shenoi et al . [ 25 ] concluded that PTN and V-taper showed no significant transportation in apical region and V-taper showed better centering ability than PTN and Hyflex. He attributed this to reduced shaft diameter and less cross-section area of V-taper file.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze canal preparation (wear, transportation, and centering ability), cone beam computed tomography was used in this study and in those by Shah et al [15], Shenoi et al [16], and Mamede-Neto et al [17], who all analyzed the same factors.…”
Section: Discussionmentioning
confidence: 99%